Computational model of enterprise cooperative technology innovation risk based on nerve network. Issue 2 (June 2018) - Yang, Changhui; Yang, Ruixia; Xu, Tingting; Li, Yinxia
Collaborative innovation has become the principal innovation method because of the puniness of the innovation strength of the enterprises. Due to the objective reality nature of the risk of enterprise collaborative technology innovation, it is necessary to take measures to prevent and indemnify the loss which the risk may bring. Because there is the complex nonlinear function mechanism between risk factors, the cooperative mode and control mechanism of enterprise collaborative innovation can be studied by nonlinear method. First, this paper analyzed the seeking method of enterprise collaborative innovation risk, and then the concept of controlling risk regulation gradient of the cooperating technological innovation under network environment was explained. And a complete controlling risk model of the cooperating technological innovation has been put forward, which is based on the wavelet and nerve network. Finally, the discussion about the conclusion of the research was given.